The effect of prenatal yoga and acupressure on lowering blood pressure in pregnant women - Siti Rahmadani Nasution; Nurul Lidya; Yunita Laila Astuti; Diana Hartaty Anggaraini (Alma Ata University Press, 2023)
Background: Hypertension in pregnancy is one of the contributors to the maternal mortality rate (MMR) in Indonesia. The combination of yoga and acupressure was expected to help pregnant women in lowering blood pressure.Objectives: This study aimed to test the combination of prenatal yoga and acupressure against blood pressure in pregnant women who had hypertension.Methods: This study was a quasi-experiment using a pre-post-test design with control group. The population in this study was all pregnant women in the Depok Regional Health Center. The inclusion criteria for this study included: pregnant women aged > 20 weeks of pregnancy, suffering from hypertension, namely systolic TD ≥140 mmHg and diastolic ≥90 mmHg. As for pregnant women who had a history of preeclampsia, had a history of bleeding in this pregnancy, pregnant women with placenta previa totalis were excluded from this study. The sample was taken by purposive sampling with the number of respondents as many as 30 pregnant women in the intervention group and 30 pregnant women in the control group. Data analysis used SPSS version 20 with descriptive and Chi-square tests for respondent characteristics. Bivariate analysis was analyzed with the Wilcoxon test, while to find out the difference in blood pressure between the two groups, the Mann-Witney U test was used.Results: Statistical results obtained that there was a significant difference in the blood pressure of pregnant women before and after yoga and acupressure. In addition, there were significant differences in blood pressure reduction between the intervention group and the control group.Conclusions: Yoga and acupressure combination was proven to reduce blood pressure. It is hoped that midwives or other health workers could implement it by teaching pregnant women, especially who suffer hypertension